2015
DOI: 10.1016/j.procs.2015.07.092
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of High Performance Work Systems and Leader-Member Exchange Quality on Employee Engagement: Evidence from a Brazilian Non-Profit Organization

Abstract: The field of strategic human resource management (SHRM) is mainly concerned with the development of HRM systems that create value to the organization and its internal customers. In this paper, we evaluate the effects of high performance work systems (HPWS) and leader-member exchange (LMX) quality on employee engagement, and also the relationship between employee engagement and turnover intention. The research involved 189 employees of a nonprofit Brazilian organization. Results from hierarchical multiple regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 13 publications
3
34
0
6
Order By: Relevance
“…-Training and development competitive advantage can be achieved, developed and maintained. This paper showed that HRM content and process must be integrated effectively in order for prescriptive models of strategic HRM Lucia Barbosa de Oliveira, Fernanda Flôres Roitman Aguiar da Silva [77] (2015)…”
Section: Employee Retentionmentioning
confidence: 99%
“…-Training and development competitive advantage can be achieved, developed and maintained. This paper showed that HRM content and process must be integrated effectively in order for prescriptive models of strategic HRM Lucia Barbosa de Oliveira, Fernanda Flôres Roitman Aguiar da Silva [77] (2015)…”
Section: Employee Retentionmentioning
confidence: 99%
“…[18] explored the emotional side of work which provided a comprehensive, emotional and behavioral components associated with an individual's performance. [19] defined it as a positive and rewarding psychological work related state, characterized by vigor, dedication, and absorption. This paper used this definition in explaining employee engagement.…”
Section: Definition Of Employee Engagementmentioning
confidence: 99%
“…[18] studied employee engagement based on components such as leadership, team, coworker relationship, training, career development and compensation. Other an indispensable attributes included organizational policies, procedures, structures, systems, and workplace wellbeing [19]. Additionally, [34] advised that in order to impact employee engagement, managers should pay attention to staff skills, knowledge and talent.…”
Section: Antecedences Of Work Engagement Based On Areas Of Work Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Ainda em relação aos correlatos da LMX, busca similar foi realizada na produção nacional (nas bases Scielo, ProQuest, Google Acadêmico, Periódicos CAPES, Pubmed, Banco de Teses e Dissertações da CAPES), sem se restringir, entretanto, a estudos do tipo meta-análise. Os resultados revelam defasagem se comparada à produção internacional, pois foram identificados apenas cinco artigos empíricos (Niemeyer & Cavazotte, 2016;Nunes & Gaspar, 2016;Oliveira & Rocha, 2017;Oliveira & Silva, 2015;Silveira & Hanashiro, 2009) e um artigo de revisão (Turano & Cavazotte, 2016). Também foram encontradas onze dissertações de mestrado e três teses de doutorado que adotaram a teoria (Amaral, 2007;Azevedo, 2014;Braga, 2012;Brant, 2012;D'Ávila, 2016;Furtado, 2016;Gonçalves, 2015;Horta, 2012;Maccarielo, 2012;Niemeyer, 2013;Pereira, 2016;Rocha, 2014;Silva, 2014;Silveira, 2007).…”
Section: Introductionunclassified